Incidence and Risk Factors of Dry Eye in a Spanish Adult Population: 11-Year Follow-Up From the Salnés Eye Study. Issue 12 (December 2018) - Millán, Alejandro; Viso, Eloy; Gude, Francisco; Parafita-Fernández, Alberto; Moraña, Noelia; Rodríguez-Ares, María Teresa
Abstract : Purpose: To estimate the incidence of dry eye (DE) and to evaluate risk factors in an adult cohort in Spain. Methods: The Salnés Eye Study (SES) was a cross-sectional population-based study of 654 subjects conducted from 2005 to 2006. After 11 years, 264 individuals (65.8% response rate) participated in SES 2. The incidence cohort consisted of 209 subjects not diagnosed with DE in SES 1 [mean age (SD) 67.6 years (±10.1), range: 51–92, women 69.4%]. DE was defined as the simultaneous presence of symptoms and at least 1 sign. A Schirmer test score ⩽5 mm, tear film breakup time ⩽10 seconds, rose bengal staining ≥3, and fluorescein staining ≥1 were considered indicative of signs. Poisson regression models were performed to evaluate risk factors. Results: The 11-year incidence of DE was 25.4% (95% confidence interval, 19.5–31.3) and that of symptoms was 31.6% (confidence interval, 25.4–37.8). DE incidence was significantly associated with age ( P < 0.05). After adjusting for age, secondary or university studies were protective factors for DE; taking anxiolytics or antidepressants and angiotensin-converting enzyme inhibitors increased the risk of symptoms; a history of hypertension, chronic obstructive pulmonary disease, or autoimmune diseases increased the risk of signs. Conclusions: The annual incidence of DE, symptoms, and signs, was found to be 2.3 per 100 person-years. The incidence of symptoms was higher than that reported in similar studies. This study suggests that some factors may increase the risk of symptoms, whereas other factors may increase the risk of signs.